Does exercise prevent major non‐communicable diseases and premature mortality? A critical review based on results from randomized controlled trials - Ballin, Marcel; Nordström, Peter (Journal of internal medicine, 2021)
Observational studies show that physical activity is strongly associated with a reduced risk of premature mortality and major non‐communicable diseases. We reviewed to which extent these associations have been confirmed in randomized controlled trials (RCTs) for the outcomes of mortality, cardiovascular disease (CVD), type 2 diabetes (T2D), and fracture. The results show that exercise does not reduce all‐cause mortality and incident CVD in older adults or in people with chronic conditions, based on RCTs comprising ∼50,000 participants. The results also indicate a lack of effect on cardiovascular mortality in people with chronic conditions, based on RCTs comprising ∼11,000 participants. Furthermore, there is inconsistent evidence regarding the effect of exercise on fractures in older adults, based on RCTs comprising ∼40,000 participants. Finally, based on RCTs comprising ∼17,000 participants, exercise reduces T2D incidence in people with prediabetes when combined with dietary modification, although evidence for the individual effect of exercise is lacking. Identified shortcomings of the current evidence include risks of publication bias, lack of high‐quality studies in certain high‐risk populations, and inconstant evidence with respect to some outcomes. Thus, additional large trials would be of value, especially with fracture as the primary outcome. In conclusion, according to current RCT evidence, exercise can prevent T2D assuming it is combined with dietary intervention. However, the current evidence shows that exercise does not prevent premature mortality or CVD, with inconsistent evidence for fractures.